Hereditary myopathies associated with hematological abnormalities. Issue 4 (5th January 2022) - Beecher, Grayson; Fleming, Mark D.; Liewluck, Teerin
Abstract: The diagnostic evaluation of a patient with suspected hereditary muscle disease can be challenging. Clinicians rely largely on clinical history and examination features, with additional serological, electrodiagnostic, radiologic, histopathologic, and genetic investigations assisting in definitive diagnosis. Hematological testing is inexpensive and widely available, but frequently overlooked in the hereditary myopathy evaluation. Hematological abnormalities are infrequently encountered in this setting; however, their presence provides a valuable clue, helps refine the differential diagnosis, tailors further investigation, and assists interpretation of variants of uncertain significance. A diverse spectrum of hematological abnormalities is associated with hereditary myopathies, including anemias, leukocyte abnormalities, and thrombocytopenia. Recurrent rhabdomyolysis in certain glycolytic enzymopathies co‐occurs with hemolytic anemia, often chronic and mild in phosphofructokinase and phosphoglycerate kinase deficiencies, or acute and fever‐associated in aldolase‐A and triosephosphate isomerase deficiency. Sideroblastic anemia, commonly severe, accompanies congenital‐to‐childhood onset mitochondrial myopathies including Pearson marrow‐pancreas syndrome and mitochondrial myopathy, lactic acidosis, and sideroblastic anemia phenotypes. Congenital megaloblastic macrocytic anemia and mitochondrial dysfunction characterize SFXN4‐ related myopathy. Neutropenia, chronic or cyclical, with recurrent infections, infantile‐to‐childhood onset skeletal myopathy and cardiomyopathy are typical of Barth syndrome, while chronic neutropenia without infection occurs rarely in DNM2 ‐centronuclear myopathy. Peripheral eosinophilia may accompany eosinophilic inflammation in recessive calpainopathy. Lipid accumulation in leukocytes on peripheral blood smear (Jordans' anomaly) is pathognomonic for neutral lipid storage diseases. Mild thrombocytopenia occurs in autosomal dominant, childhood‐onset STIM1 tubular aggregate myopathy, STIM1 and ORAI1 deficiency syndromes, and GNE myopathy. Herein, we review these hereditary myopathies in which hematological features play a prominent role.